Analisis Strategi Pembelajaran Matematika di Sekolah Dasar - Annisa Dea Apriliana; Mayang Kholismira Sabila; Nadya Queenisafitri; Satria Aji Samaratungga; Avista Minda Saujana (Prosiding Konferensi Ilmiah Dasar, 2026)
Mathematics plays an important role in elementary education because it develops students' logical, critical, creative, and systematic thinking skills. However, mathematics learning in elementary schools still faces various challenges, including students' difficulties in understanding abstract concepts, low learning motivation, and the dominance of teacher-centered instruction. Therefore, selecting appropriate learning strategies is essential to improve the quality of mathematics instruction. This study aims to analyze various mathematics learning strategies implemented in elementary schools through a literature review approach. The study collected and analyzed relevant national and international journal articles published between 2016 and 2026. Data analysis was conducted through literature identification, selection, classification, comparison, and synthesis. The findings indicate that five learning strategies are widely implemented in elementary mathematics education, namely Problem Based Learning, Realistic Mathematics Education, Discovery Learning, Cooperative Learning, and Problem Solving. Each strategy has distinctive characteristics, advantages, and limitations. Overall, these strategies contribute positively to improving conceptual understanding, critical thinking, mathematical reasoning, problem-solving ability, learning motivation, collaboration, and student learning outcomes. The study concludes that no single strategy is universally effective for all mathematics topics.